Centro de reconocimiento cultural estatal indígena (2021)
This project is located in the Valle del Cauca region, specifically in the city of Palmira; implanted in the northern area of ​​the same where it has the road connections of Route 25 and the AV. Carbonera, which connect with two important cities that are Buga and Cali, is located in this place as a result of the use of a specific material from the region (sugar cane), managing to solve the cultural and environmental problems of three indigenous communities. from the Valle del Cauca region (Chami, the Wuonaan and the Naza), since the waste of said material (cane fiber) generates an impact and damages in their settlements such as proliferation of pests, disorder in their habitat, bad odors and an invasion of this plant in its territory.